Control of timing, rate and bursts of hippocampal place cells by dendritic and somatic inhibition - Royer, Sebastien; Zemelman, Boris V.; Losonczy, Attila; Kim, Jinhyun; Chance, Frances; Magee, Jeffrey C.; Buzsaki, Gyoergy (NATURE PUBLISHING GROUP, 2012)
A consortium of inhibitory neurons control the firing patterns of pyramidal cells, but their specific roles in the behaving animal are largely unknown. We performed simultaneous physiological recordings and optogenetic silencing of either perisomatic (parvalbumin (PV) expressing) or dendrite-targeting (somatostatin (SOM) expressing) interneurons in hippocampal area CA1 of head-fixed mice actively moving a treadmill belt rich with visual-tactile stimuli. Silencing of either PV or SOM interneurons increased the firing rates of pyramidal cells selectively in their place fields, with PV and SOM interneurons having their largest effect during the rising and decaying parts of the place field, respectively. SOM interneuron silencing powerfully increased burst firing without altering the theta phase of spikes. In contrast, PV interneuron silencing had no effect on burst firing, but instead shifted the spikes' theta phase toward the trough of theta. These findings indicate that perisomatic and dendritic inhibition have distinct roles in controlling the rate, burst and timing of hippocampal pyramidal cells.
Keywords: CA1 PYRAMIDAL NEURONS; PHASE-PRECESSION; THETA OSCILLATIONS; IN-VIVO; SYNAPTIC PLASTICITY; INTERNEURONS; DYNAMICS; MECHANISMS; SEQUENCES; CORTEX